A Comparison of Angular Values of the Pelvic Limb with Normal and Medial Patellar Luxation Stifles in Chihuahua Dogs Using Radiography and Computed Tomography - Phetkaew, Thitaporn; Kalpravidh, Marissak; Penchome, Rampaipat; Wangdee, Chalika (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective This article aimed to determine and compare the angular values of the pelvic limb in normal and medial patellar luxation (MPL) stifles in Chihuahuas using radiography and computed tomographic (CT) scan, to identify the relationship between pelvic limb angles and severity of MPL. In addition, radiographic and CT images were compared to determine the more suitable method of limb deformity assessment.Methods Sixty hindlimbs of Chihuahuas were divided into normal and grade 1, 2, 3 and 4 MPL groups. The pelvic limb angles in frontal and sagittal planes were evaluated on radiography and CT scan. Femoral and tibial torsion angles (FTA and TTA) were evaluated only by CT scan. All angles were compared among normal and MPL stifles and between radiography and CT scan.Results Based on the CT scan, the mechanical lateral distal femoral angle (mLDFA), anatomical caudal proximal femoral angle (aCdPFA), and TTA were related to the severity of MPL. The mLDFA and TTA were significantly increased (p < 0.05) in grade 4 MPL, while the aCdPFA was significantly decreased in grade 2, 3 and 4 MPL groups. There were significant differences of many angles between radiography and CT scan.Clinical Significance The angles related to MPL in Chihuahuas are aLDFA, mLDFA, aCdPFA and TTA. Radiography had some limitations for evaluating pelvic limb angles. The caudocranial radiograph is recommended for the assessment of the distal femoral angles, while the craniocaudal radiograph is for the tibial angles.
Keywords: Chihuahua; medial patellar luxation; pelvic limb deformity; computed tomography; radiography